LEARNING STRATEGIES USED BY STUDENTS IN SPEAKING CLASS AT LC (Language Center) IN KAMPUNG INGGRIS PARE, KEDIRI - Arisanti Locita; Agung Wicaksono; Sulistyani (Nusantara Education, 2023)
This research aims to describe the learning strategies used by students in LC (Language Center), Kampung Inggris Pare, Kediri. The research question is what the learning strategies used by students in the intensive 2-week program in LC Course, Kampung Inggris Pare, Kediri? There are some aspects that should be considered in learning to speak. It includes fluency, pronunciation, grammar, accuracy, and appropriateness’. The subject of this research is B6 class students who were in the intensive 2-week program in LC which consist of 7 students. This research used a descriptive qualitative method and used two data collection techniques in the form of questionnaires and documentation. The findings of this research revealed there are six strategies that were used by students when learning speaking English and the researcher concludes that the social strategy is mostly used by students with a total of 46,67%. The conclusion of this research that the social strategy is commonly used by students because they prefer to involve other people in their learning. The researcher suggests to the next researcher can further develop the theories and findings found in this study and also hopes the students can know what their correct learning strategies are to support their learning.